Iron nutrition and virulence in Xanthomonas oryzae pv. oryzae - and R. SRIDHAR, M.M. ANSARI (Indian Phytopathology, 2002)
The significance of iron on the growth and virulence of Xanthomonas oryzae pv. oryzae the causal agent of bacterial leaf blight of rice was examined. Lag phase was reduced with Fe supplement in the growth medium. The lag phase was more without iron, and also when the concentration of Fe exceeds 8.0 /-lg/ml. The optimum concentration of iron for the growth of the bacterium was 4.0 mg Fell. Iron nutrition to the bacterium also enhanced the indole-3-acetic acid (IAA) production in the culture filtrate. However, the higher concentration of iron i.e. 20 mg/l (equivalent to 100 mg FeS0 4 II) was found to be inhibitory for IAA production. Isolate gained virulence in causing leaf blight when cultured with increasing concentrations of iron up to 8.0 mg of Fell in presence of toÂ·3 M tryptophan. Addition of tryptophan either as medium for inoculum or added to the soil decreased the incubation period for wilting in both susceptible and resistant cultivars and enhanced the per cent wilting in susceptible only. Iron was determined as the factor influencing virulence of the Xantltomonas oryzae pv. oryzae.